N-terminal pro-brain natriuretic peptide as a predictive marker of short-term mortality in sepsis - Amit Kumar; Rajesh Chetiwal; Shweta Tanwar (MGM Journal of Medical Sciences)
Background: Sepsis remains a major global health concern, contributing to significant morbidity and mortality, particularly in low- and middle-income countries where healthcare resources are limited. N-terminal pro-brain natriuretic peptide (NT-proBNP), a biomarker widely studied in heart failure, has shown potential in sepsis but remains underexplored. This study investigates the prognostic significance of NT-proBNP in sepsis, focusing on its role in risk stratification and predicting short-term outcomes. Materials and Methods: A prospective study was conducted in a tertiary care hospital’s medical intensive care unit in North India from January 2021 to January 2024. A total of 354 patients meeting the Sepsis-3 criteria were enrolled. Patients with pre-existing cardiac dysfunction, chronic renal failure, advanced liver disease, or immunosuppression were excluded. NT-proBNP levels were measured at admission and analyzed regarding clinical and laboratory parameters, disease severity scores (Sequential Organ Failure Assessment [SOFA], APACHE II), and 28-day mortality. Statistical analyses included receiver operating characteristic (ROC) curve analysis, Kaplan–Meier survival estimates, and Cox regression analysis. Results: Median NT-proBNP levels were significantly higher in non-survivors (6234 pg/mL) compared to survivors (1850 pg/mL, P < 0.0001). NT-proBNP demonstrated a positive correlation with SOFA (r = 0.69, P < 0.0001) and APACHE II scores (r = 0.42, P = 0.002) and a negative correlation with left ventricular ejection fraction (r = −0.25, P = 0.010). ROC analysis yielded an area under the curve of 0.925, with an NT-proBNP cutoff of 5000 pg/mL, achieving a sensitivity of 86.4% and specificity of 72.8%. Kaplan–Meier analysis revealed significantly lower survival rates for patients with NT-proBNP levels ≥5000 pg/mL (P < 0.01, log-rank test). Cox regression analysis identified NT-proBNP as an independent predictor of 28-day mortality (P = 0.02). Conclusion: NT-proBNP is a valuable prognostic biomarker in sepsis, correlating strongly with disease severity and mortality risk. These findings underscore the potential of NT-proBNP-based risk stratification to enhance sepsis management and improve patient outcomes.